Multi-omics reveals the effects of dietary supplementation with Bupleuri radix branch powder on gut microbiota and lipid metabolism: insights into gut microbial-muscle interactions - Haiyan Li; Cheng Pan; Fuqiang Wang; Zengkai Li; Khuram Shahzad; Yanping Huang; Wangsheng Zhao (Microbiology Spectrum)
ABSTRACT Improving livestock growth and raising the quality of livestock products have attracted much attention owing to the market’s growing need for livestock products. Bupleuri Radix branches powder (BR) has a variety of health characteristics, but its effects on ruminant growth and animal product quality are still uncertain. This study explored the effects of BR on growth performance, health status, gut microbiota, and muscle lipid metabolism of Shaanxi fine-wool sheep (SFS), and examined the interaction between gut microbiota and lipid metabolism through correlation analysis. The results indicated that BR can regulate the immune function, intestinal VFAs, and enzyme activity of FSF by improving the gut microbiota, thereby affecting its muscle lipid metabolism. The lipid metabolite TG showed a strong positive correlation with the gut microbes Bacteroides and Fibrobacter, while Phosphatidylethanolamine and Phosphatidyl serine (PE and PS) showed a significant negative correlation with Fibrobacter. The above results indicate that gut microbiota and lipid metabolites interact with each other. BR has the effects of promoting SFS growth, improving body health, and improving meat quality. These findings offer new insights into improve animal growth performance and livestock product quality in modern farming.IMPORTANCEEnhancing livestock growth performance and improving meat quality are important guidelines for the development of the current animal husbandry industry; thus, we explored a comprehensive study of Bupleuri Radix (BR) on growth performance, gut microbiology, and muscle lipid metabolism in Shaanxi fine-wool sheep (SFS). Our research has found that BR could improve the growth performance of SFS and meat quality by affecting gut microbes. This study provides new solutions to improve the economic efficiency of animal husbandry.